A DOCTRINAL PROMENADE INTO THE HEART OF THE BUSINESS CYCLE THEORY: BRIEF AUSTRIAN HALT - Elena Bianca Vieru; Ion Pohoata (European Scientific Journal, ESJ, 2013)
Throughout this paper we propose a brief doctrinaire promenade starting with the Monetarist approach, reaching the Keynesian doctrine and finishing with the point of maximum interest, namely the Austrian perspective regarding imbalances. Exhaustively passing through the theories mentioned above, along with their fundamental perspective regarding the phenomenon of economic cycles, does not represent the basis for the current paper. The specialized literature has no shortage of such work. The purpose of this research is to highlight the explanatory strength of the Austrian business cycle theory, establishing the reasons for considering it the best cemented one in regard to the recurrence of crises. For being able to arrive to such a judgment, we employed a contradictory approach between the Austrian doctrine and the Keynesist, respectively, the Monetarist one. The conclusions we reached reflect a healthy Austrian vision in regard to addressing the issue of economic crises. Therefore, complying the basic Austrian principles can ensure prosperity to the economies that decide to apply them.